Hepatitis C Virus Infection Cycle-Specific MicroRNA Profiling Reveals Stage-Specific miR-4423-3p Targets RIG-I to Facilitate Infection - Qian, Xijing; Wu, Bingan; Xu, Chen; Qi, Zhongtian (Frontiers in Cellular and Infection Microbiology, 2022)
Hepatitis C virus (HCV) infection is one of the main reasons of chronic liver diseases, the disorders of which involve multiple pathological processes and elements including host factors such as non-coding small RNAs. Although several genes have been reported to be correlated with HCV infection, the potential regulatory network has not been deciphered clearly. By small RNA sequencing, we clarified the expression profile of microRNAs (miRNAs) in HCV-infected Huh7 and Huh7.5.1 cells, and identified 6 dysregulated miRNAs with the same expression trend and 32 dysregulated miRNAs with different expression trends during different stages of HCV life cycle. By looking into each infection stage, we found that 6 miRNAs were entry stage specific, 4 miRNAs were replication stage specific, and 1 miRNA was related to the transmission stage. Moreover, due to the nature that Huh7.5.1 cells bear retinoic acid-inducible gene 1 (RIG-I) mutation which causes less production of interferons (IFNs), we here focused on the miRNAs of different trend to decipher the RIG-I/IFN specific miRNAs. Among them, miR-4423-3p showed significant promotive effect on HCV infection by suppressing RIG-I/IFN pathway through direct binding to RIG-I mRNA. Together, the results displayed novel insights into the miRNA regulatory networks in HCV infection and progression, thus providing a prosperous perspective into the establishment of novel therapeutic and diagnostic targets of the disease.